Exact-Dimensional Property of Density of States Measure of Sturm Hamiltonian. (19th March 2017) - Qu, Yanhui
Abstract: For frequency α of bounded type and coupling λ>20, we show that the density of states measure N_α, λ of the related Sturm Hamiltonian is exact upper and lower dimensional, however, in general it is not exact dimensional.